PENGEMBANGAN EKONOMI LOKAL MELALUI KEWIRAUSAHAAN KREATIF - Sakinah, Fistiawirzani; Fahlevi, Rizal; Rahmawati, Rafika (An-Nizam, 2024)
Local economic development through creative entrepreneurship is the main focus of various efforts to improve community welfare at the local level. The aim of this service is to encourage local economic growth by utilising the potential of creativity and innovation owned by local communities. Through a participatory approach, the goal is realised by involving various stakeholders, ranging from local businesses to local government, in the process of strategy development and programme implementation. The service method used involves community education and training to understand the characteristics of the local economy and evaluate the potential and obstacles in the development of creative entrepreneurship. In addition, training and mentoring to prospective entrepreneurs as well as networking and promotion of local products to improve market access were also conducted. The results of the service showed that creative entrepreneurship is able to make a significant contribution in increasing the income and welfare of local communities. With the support of various parties, an environment conducive to the growth of creative businesses at the local level was created. In addition, there is also an increased awareness of the importance of preserving local culture and the environment through sustainable business practices. However, achieving sustainable success requires strong commitment and co-operation between various stakeholders, as well as policies and regulations that support the development of creative entrepreneurship at the local level.